2012
DOI: 10.2337/dc11-1746
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial to Assess the Efficacy and Safety of Real-Time Continuous Glucose Monitoring in the Management of Type 1 Diabetes in Young Children Aged 4 to <10 Years

Abstract: OBJECTIVEContinuous glucose monitoring (CGM) has been demonstrated to improve glycemic control in adults with type 1 diabetes but less so in children. We designed a study to assess CGM benefit in young children aged 4 to 9 years with type 1 diabetes.RESEARCH DESIGN AND METHODSAfter a run-in phase, 146 children with type 1 diabetes (mean age 7.5 ± 1.7 years, 64% on pumps, median diabetes duration 3.5 years) were randomly assigned to CGM or to usual care. The primary outcome was reduction in HbA1c at 26 weeks by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
218
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(235 citation statements)
references
References 18 publications
12
218
3
2
Order By: Relevance
“…33,34 A follow-up study by The Diabetes Research in Children Network (DIRECNET) Study Group reported by Mauras et al tested CGM in 146 children with type 1 diabetes. 35 In this 26-week study, 36% of the participants used MDI. There was no change in HbA1c or hypoglycemia in either the CGM or control groups.…”
Section: Cgm In Type 1 Diabetes Treated With MDImentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 A follow-up study by The Diabetes Research in Children Network (DIRECNET) Study Group reported by Mauras et al tested CGM in 146 children with type 1 diabetes. 35 In this 26-week study, 36% of the participants used MDI. There was no change in HbA1c or hypoglycemia in either the CGM or control groups.…”
Section: Cgm In Type 1 Diabetes Treated With MDImentioning
confidence: 99%
“…A key factor in the success of CGM to lower HbA1c and to reduce hypoglycemia is clearly wear time and use of trend arrows and alarms to help guide therapy and to provide warning for hyperglycemia or impending hypoglycemia. 35 Riveline et al reported a three-arm study comparing standard of care versus physician-or patient-led groups using CGM. 36 The study population from 19 diabetes care centers in Europe included 178 adults, mean age 36.4 -13.6 years, diabetes duration about 17 years, 47.2% using MDI, mean HbA1c 9.0% -0.9%.…”
Section: Cgm In Type 1 Diabetes Treated With MDImentioning
confidence: 99%
“…Satisfaction with treatment is high among parents and children with type 1 diabetes, whether the control of diabetes is improved [51] or not (evidencing the importance of low glucose alarms in particular in young children) [48]. The Onset Trial study shows, with validated QoL scales, an improvement in well-being and QoL in children and a decrease in parental depression in the year following the diagnosis, in comparison with the group receiving the same treatment with pumps without sensors [47].…”
Section: Satisfaction With Treatment and Quality Of Lifementioning
confidence: 99%
“…Seven of the studies focus on adults and children/ adolescents and four focus only on a paediatric population [24,31,47,48]. The international recommendations on the use of CGM with children and adolescents have just been published [49].…”
Section: Clinical Efficacy In Children and Adolescents With Type 1 DImentioning
confidence: 99%
“…The group found a statistically significant, although clinically small difference in HbA1c from 8.6% -1.5% at baseline to 8.4% -1.3%. 8 In 2003 Ludvigsson and Hanas performed a controlled crossover study with 27 patients with diabetes age [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in which an open and masked study arm wore CGM for 3 days every 2 weeks. The open study arm received insulin dose adjustment based on the glycemic profiles obtained from the CGM.…”
Section: Type 1 Diabetesmentioning
confidence: 99%